Investigating the Lid Effect on the Generation of Ocean Island Basalts: 1. Geochemical Trends - Shihao Jiang; Rhys Hawkins; Mark J. Hoggard; D. Rhodri Davies; Ian H. Campbell (Geochemistry, Geophysics, Geosystems, 2024)
Abstract Ocean island basalts (OIBs) are generated by mantle plumes, with their geochemistry controlled by a combination of source composition, temperature, and thickness of overlying lithosphere. For example, OIBs erupting onto thicker, older oceanic lithosphere are expected to exhibit signatures indicative of higher average melting pressures. Here, we quantitatively investigate this relationship using a global data set of Neogene and younger OIB compositions. Local lithospheric thicknesses are estimated using theoretical plate‐cooling models and Bayes factors are applied to identify trends. Our findings provide compelling evidence for a correlation between OIB geochemistry and lithospheric thickness, with some variables (SiO2, Al2O3, FeO, Lu) showing linear trends that can be attributed to increasing average melting pressure, whereas others (CaO, La, λ0, and λ1) require a bi‐linear fit with a change in gradient at ∼55 km. Observed variations in highly incompatible elements are consistent with degrees of melting that decrease with increasing lithospheric thickness, as expected. Nevertheless, at thicknesses beyond ∼55 km, the implied degree of melting does not decrease as rapidly as is suggested by theoretical expectations. This observation is robust across different lithospheric thickness estimates, including those derived from seismic constraints. We infer that at thicknesses exceeding ∼55 km, weak plumes fail to effectively thin overlying lithosphere and/or produce insufficient melt to erupt. This is supported by independent estimates of plume buoyancy flux, indicating that OIB magmatism on older lithosphere may be biased toward hotter plumes. In addition, we find evidence for a “memory effect” of incomplete homogenization of melts during their ascent.